Anti-hyperalgesic activity of Ficus deltoidea in an animal model of migraine - Salihan, Safuraa; Mohd Moklas, Mohamad Aris; Khalid, Mohamed Hanief; Chiromaa, Samaila Musa; Sulaiman, Mohd Roslan; Baharuldin, Mohamad Taufik Hidayat (National Institute of Science Communication and Policy Research, 2024)
Migraine is one of the most common primary headaches, causing significant morbidity to its sufferers. Ficus deltoidea (FD) is a plant that is traditionally used in Malaysia to treat headaches. This study evaluated the potentials of FD on attenuating hyperalgesia in nitroglycerin (NTG)-induced mice model of migraine and its related C-fos expression. This study was divided into phases. In Phase1, NTG-induced mice model of migraine was constructed by a single dose of NTG 10 mg/kg and validated through formalin and hot plate tests, followed by evaluation of the level of C-Fos in their trigeminal nucleus caudalis (TNC) through immunoblotting. In Phase 2, the effect of FD (50, 100, and 200 mg/kg) on hyperalgesic behaviours and levels of C-Fos in TNC of NTG-induced mice was evaluated and compared with NTG-induced mice. The results showed a significant increased (p <0.05) of nociceptive behaviours in both formalin and hot plate tests and increased (p <0.05) C-Fos expression in TNC were observed in NTG-induced mice when compared to control, sumatriptan and topiramate groups. However, treatments with aqueous extract of FD (100 and 200 mg/kg) significantly reversed all the observed changes. In conclusion, FD dose-dependently attenuated nociceptive behaviours in NTG-induced mice model of migraine and inhibition of C-Fos production in TNC of the mice. This shows the potential of FD to be used for future development as a natural therapeutic agent for migraines, supporting its traditional use in relieving headache.